The Influence Of The Management Control System On The Performance Of Class IIB Bengkulu Private Employees - Putra, Kevin Arigi; Susanti, Neri; Astuty, Kamelia (Journal of Research in Social Science and Humanities, 2024)
The aim of this research is to find out "The Influence of the Management Control System on the Performance of Class Iib Bengkulu Detention Center Employees" so that this research is more focused and does not get away from the problem discussed, namely: "Management Control System on the Performance of Bengkulu Class Iib Detention Center Employees". Employee performance can be objectively and accurately evaluated through performance level benchmarks. This measurement means giving employees the opportunity to know their performance level. Makes it easier to review employee performance, This research uses quantitative research methods. The sample in this study amounted to 69 respondents. The regression equation obtained is as follows: Y = 38,914+1,174 38,914. The Management Control System (X) regression coefficient of 1.174 states that every one unit increase in the value of the Management Control System variable can increase the value of the Employee Performance variable (Y) by 1.174, assuming that the Management Control System variable (X) remains or = 0. The Management Control System influences employee performance with a coefficient value of ? 1.174 and a significance of 0.034 0.05, which means that the higher the Management Control System, the higher the performance of the Bengkulu Class IIB Detention Center. In other words, every time the Management Control System is improved, employee performance will increase, meaning that the Management Control System (X1) and Employee Performance (Y) have a positive and significant relationship.